The Effect of Lower Body Positive Pressure on Left Ventricular Ejection Duration in Patients With Heart Failure. Issue 4 (23rd November 2018) - Avadhani, Sriya; Ihsan, Muhammad; Nunez, Arismendy; Kamran, Haroon; Singh, Sahib; Hasan, Zohair; Salciccioli, Louis; Kral, John G.; Godwin, Ellen M.; Lazar, Jason
Lower body positive pressure (LBPP) treadmill activity might benefit patients with heart failure (HF). To determine the short-term effects of LBPP on left ventricular (LV) function in HF patients, LV ejection duration (ED), a measure of systolic function was prospectively assessed in 30 men with stable HF with LV ejection fraction ≤ 40% and 50 healthy men (N). Baseline measurements (100% body weight), including blood pressure (BP), heart rate (HR) and LVED, obtained via radial artery applanation tonometry, were recorded after 2 minutes of standing on weight support treadmill and after LBPP achieving reductions of 25%, 50%, and 75% of body weight in random sequence. Baseline, HR, and LVED (251 ± 5 vs 264 ± 4 ms; P = .035) were lower in the HF group. The LBPP lowered HR more (14% vs 6%, P = .009) and increased LVED more (15% ± 7% vs 10% ± 6%; P = .004) in N versus HF. Neither group had changes (Δ) in BP. On generalized linear regression, the 2 groups showed different responses ( P < .001). Multivariate analysis showed %ΔHR ( P < .001) and HF ( P = .026) were predictive of ΔED ( r 2 = 0.44; P < .001). In conclusion, progressive LBPP increases LVED in a step-wise manner in N and HF patients independent of HR lowering. The ΔLVED is less marked in patients with HF.